Implementation and improvement of policies for building healthy cities in China - Quansheng Wang; Guoqing Han; Lansong Huang (Frontiers in Public Health)
Background and purposeWith the promotion of the World Health Organization, China has also launched a healthy city construction campaign. However, healthy city construction needs to formulate a series of policies. How can the current healthy city policy in China be further improved to provide a policy basis for healthy city construction?Materials and methodsCollected here are policy texts from the Central People’s Government and local government of the People’s Republic of China on healthy cities from 2009 to 2023. This paper adopts the policy tool analysis method to design a two-dimensional analysis framework of the “policy tool-construction domain.” There are three types of policy tools: demand-oriented, supply-oriented, and environmental-oriented. The field of healthy city construction is based on five fields defined by WHO: healthy population, health service, healthy environment, healthy culture, and healthy society. The policy text was coded and analyzed by Nvivo software.ResultsAccording to the coding analysis of policy texts, among the three types of policy tools, supply-oriented policies account for 60.5%, environmental policies account for 29.1%, and demand-oriented policies account for 10.4%. In the five areas of healthy city construction, healthy environment accounted for 23.7%, healthy society accounted for 12.3%, health services accounted for 39.1%, healthy population accounted for 13%, and health culture accounted for 11.9%. From the two-dimensional perspective of policy tools and the field of healthy city construction, the five fields of healthy city construction have different emphases on the application of three different types of policy tools.ConclusionCurrently, the supply-oriented policy, the demand-oriented policy, and the environmental policy tools are used comprehensively in healthy city construction in China. The proportion of supply-oriented policy is high, which emphasizes the government’s intervention and neglects the participation of individuals and social organizations. The use of policy tools is not balanced in the five different areas of healthy city construction, which to some extent limits the effect of policy implementation and strengthens the overall effect of the healthy city construction policy.